Major gene families in humans and their evolutionary history - Niimura, Yoshihito; Nei, Masatoshi (Henry Stewart Talks, 2007)
Multigene family, Olfactory Receptors (ORs), OR genes in humans, Comparison of OR genes between humans and mice, Evolution of OR genes in vertebrates, Other chemosensory receptor genes
Archived at 2021/02/25